PHYSICAL PROPERTIES AND LIMESTONE TEST OF RICE BRAN MIXTURE WITH LIMESTONE FLOUR - SULAIMAN M. I. N.; I. HERNAMAN; A. BUDIMAN; U. ROSANI (Majalah Ilmiah Peternakan)
This study aims to determine the effect of the addition of limestone flour with rice bran on the physical proper- ties and Limestone Test. This study used a Complete Random Design (CRD) with 6 treatments and was repeated 5 times. The levels of limestone flour addition in the treatments were of 0%, 5%, 10%, 15%, 20%, and 25%. The research data were processed using Analysis of Variance (ANOVA) and continued with Dunnett’s test with P0 as the control treatment, as well as regression and correlation tests. The results showed that the addition of limestone flour had a significant effect (P<0,05) on particle specific gravity, bulk density, porosity, and limestone test. The conclusion of this study is that the higher the addition of limestone flour, the particle specific gravity value, bulk density, porosity, and limestone test will increase with correlation values (r) of 0,8643, 0,9873, 0,7395, and 0,9837, indicating strong correlations.